Parenteral Antimicrobial Treatment Diminishes Fecal Bifidobacterium Quantity but Has No Impact on Health in Neonatal Dairy Calves: Data From a Field Trial - O'Keefe, Olivia C.; Moore, Dale A.; McConnel, Craig S.; Sischo, William M. (Frontiers in Veterinary Science, 2021)
There is evidence that neonatal calves are over treated with antimicrobials that may disrupt colonization of their gastrointestinal tract (GIT) microbiota. The study objectives were to assess the decision-making process of antimicrobial use on a commercial dairy and impacts of parenteral antibiotics on dairy calves’ GIT Bifidobacterium and calf health. Unhealthy pre-weaned dairy calves were enrolled based on farm personnel identification with age-matched healthy calves. Half the calves in each group were treated with IM ampicillin and half were given supportive therapy as needed. Health scores (appetite, fecal consistency, attitude, and temperature) were recorded twice daily throughout the study. Based on objective clinical observations plus fecal dry matter, the 121 enrolled calves were reclassified into 3 health categories: healthy, uncomplicated diarrhea (bright attitude and good appetite but with diarrhea), and sick. This resulted in 6 post enrollment health categories. Calves were followed for 14 days post-enrollment and fecal samples collected at 6 time points. Bifidobacterium was quantified using quantitative PCR from fecal samples collected throughout the study. The objective criteria for disease definition reclassified many “unhealthy” calves as uncomplicated diarrhea. Including all calves, on average, the quantity of Bifidobacterium decreased from the day of enrollment (median 8 days of age) across time to 14 days post-enrollment. Calves given an antibiotic the day of enrollment had a greater decrease in Bifidobacterium 4 and 9 days later relative to enrollment Bifidobacterium compared to untreated calves. Sick calves or those with uncomplicated diarrhea at enrollment were more likely to have low Bifidobacterium counts on that day and if classified as sick at enrollment to be categorized as sick or uncomplicated diarrhea 4 days later following a 3-day treatment protocol. Our results indicate that relying on farm personnel to identify morbidity may lead to some clinical misclassification. There was no indication that antimicrobials affected subsequent health outcomes. These results highlight the importance and difficulty in assigning appropriate illness classification on farms and point to a need to develop better point of care diagnostics to help the industry improve stewardship of antimicrobials and mitigate their effect on GIT flora.